The role of needs-supplies fit and job satisfaction in predicting employee engagement - Ameer A. Basit,; Rasidah Arshad, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Employee engagement has become a key concern for organizations as it provides value for sustainable competitive advantage. Fully engaged workforce is not only important in helping organizations flourish in good times but also relevant in helping organizations persevere during tough times. However, the main challenge for employers is to motivate and keep their employee engaged. Recent organizational behaviour studies emphasize the importance of environmental influences in understanding employees attitudes and behaviours. Consistent with this development, the present study seeks to examine the role of needs-supplies fit and job satisfaction in predicting employee engagement. Drawing from the self-in-role view and social exchange theory, it was hypothesized that needs-supplies fit predicts employee engagement, and the relationship between the two constructs is mediated by job satisfaction. Using a self-administered survey, data were obtained from 161 employees of a large public university in Malaysia. The results fully supported the hypothesized relationships. Implications for theory and practice are discussed.